Magnetic Resonance Imaging Features of Pediatric Coxsackievirus Encephalitis - Yang-Kai Fan; Yu-Peng Liu (Journal of the Belgian Society of Radiology, 2019)
Coxsackievirus, a common pathogen causing pediatric infection, typically causes a mild, nonspecific illness with low-grade fever, but can cause severe illness on rare occasions. Encephalitis is an uncommon but important complication of coxsackievirus infection. The magnetic resonance imaging (MRI) findings of coxsackievirus B3 (CVB3) encephalitis have not been reported in the literature, and there are few descriptions of MRI findings of encephalitis induced by coxsackieviruses of other serotypes. We report the MRI findings of CVB3 encephalitis in a two-year-old girl, review the MRI findings in previously reported cases of pediatric coxsackievirus encephalitis, and present the MRI characteristics of coxsackievirus encephalitis.